AUTOMATION OF COTTON CLEANING PROCESS THROUGH INTELLIGENT SYSTEMS - Oybek Kholmatov; Abdulazizov Dostonbek (European Science Publishing, 2024)
The article discusses the application of intelligent systems in automating the cotton cleaning process in the textile industry. It highlights the benefits of using robotics, artificial intelligence, and computer vision technologies to enhance efficiency, accuracy, and productivity in cotton cleaning. The article emphasizes the advantages of automating this traditionally labor-intensive process, including improved efficiency, enhanced accuracy, cost reduction, worker safety, and data-driven insights. It also addresses some challenges and considerations associated with system integration, maintenance, adaptability, and initial investment. Overall, the article provides a comprehensive overview of how intelligent systems can revolutionize the cotton cleaning process, leading to higher productivity and improved product quality in the textile industry.
Keywords: Automation, cotton ginning, intelligent systems, robotics, artificial intelligence, computer vision, textile industry.